Model Tourist Engagement melalui Nostalgic Emotion dan Memorable Tourism Experience (Survei pada Destinasi Wisata Alam Air Panas di Jawa Barat) - Rahyuniati Setiawan, - (2022)
The outbreak of the COVID-19 virus has changed the landscape of the tourism industry and shifted the behavior of tourists who have adapted to new normal conditions. So, business people in the tourism industry must adapt to the new normal 'disruption' to survive and rise from adversity. The purpose of the study was to obtain findings on how tourist engagement models through nostalgic emotion and memorable tourism experiences. This study uses a quantitative approach, with the type of research in the form of descriptive and verification. Survey of 400 visitors to natural hot springs in West Java. Data analysis used a structural equation model approach. The results of the descriptive analysis of the novelty attribute destination average achievement were measurable in the excellent category, tourist engagement, city image, memorable tourism experience the average achievement was measured in the good category, while the nostalgic emotion is sufficient category. Therefore, the models have implications for increasing tourist engagement in hot spring natural tourist destinations. The novelty of this research is the discovery of a model for increasing tourist engagement in natural hot spring tourist destinations in West Java.